Streamlining the process of Newborn and Infant Physical Examination (NIPE). Issue 5 (31st July 2018) - Ghabra, Karim; Ahmed, Molla Imaduddin; McDevitt, Katharine; Al-Sabbagh, Afraa
Abstract : This quality improvement project helped streamline the process of newborn and infant physical examinations on maternity inpatient ward and improved patient journey and workforce satisfaction.